Analysis of Financial Performance at PT. Indofood Sukses Makmur Tbk In Makassar - Hardiyono, Hardiyono; Halik, Maria Yessica (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2024)
Financial Performance Analysis at PT. Indofood Sukses Makmur Tbk. This research aims to assess the financial performance of PT. Indofood Sukses Makmur from 2018 to 2021 using the data analysis method of liquidity ratios, solvency ratios, activity ratios, profitability ratios and profitability ratios. The type of research used in this research is quantitative data sourced from secondary data. The results of the research are: 1) the level of liquidity, which in terms of the ratio, is categorized as quite good. 2) the level of solvency in terms of the ratio is categorized as good. 3) the level of activity in terms of the ratio is categorized as good. 4) the level of profitability in terms of the ratio is categorized as very good.